Description of the System of Underground Transportation by Moving Chain, Adopted At The Hasard Gollierieis; Belgium - William P. Blake (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1874)
AMONG the many interesting objects to be seen at the Vienna Exhibition last summer, the model of the system of underground transportation by a continually moving chain, adopted at the Hasard collieries, at Micheroux, near Liége, Belgium, was one of the most attractive, and full of valuable suggestion to mining engineers. These collieries are under the superintendence of the celebrated